Circularly Polarized Rectangular Microstrip Patch Antenna with Finite Ground Plane - Sanyog Rawat; Kamlesh Kumar Sharma (International Journal of Informatics and Communication Technology (IJ-ICT), 2015)
In this paper a new geometry of patch antenna is proposed with improved bandwidth and circular polarization. The radiation performance of circularly polarized rectangular patch antenna is investigated by applying IE3D simulation software and its performance is compared with that of conventional rectangular patch antenna. Finite Ground truncation technique is used to obtain the desired results. The simulated return loss, axial ratio and smith chart with frequency for the proposed antenna is reported in this paper. It is shown that by selecting suitable ground-plane dimensions, air gap and location of the slits, the impedance bandwidth can be enhanced upto 10.15 % as compared to conventional rectangular patch (4.24%) with an axial ratio bandwidth of 4.05%.